To solve a problem like this, you can use a method called cross-multiplying. This is when you multiply the denominator of the first fraction by the numerator of the other and then multiply the two remaining numbers.
[tex] \frac{3}{4} = \frac{x}{6} [/tex] Multiply 3 by 6 and multiply 4 by x.
4x = 18 Divide by 4.
x = [tex] \frac{18}{4} [/tex] Simplify!
x = [tex] \frac{9}{2} [/tex]
You can check this by comparing the fractions with [tex] \frac{9}{2} [/tex] in the place of x.
[tex] \frac{3}{4} = \frac{ \frac{9}{2} }{6} [/tex] Divide [tex] \frac{9}{2} [/tex] by 6 ( [tex] \frac{9}{2} [/tex] times [tex] \frac{1}{6} [/tex]).
[tex] \frac{3}{4} = \frac{9}{12} [/tex] Simplify!
[tex] \frac{3}{4} = \frac{3}{4} [/tex]
The fractions are equal, so x = [tex] \frac{9}{2} [/tex] .